2002
DOI: 10.3748/wjg.v8.i1.168
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of glutamine on intestinal barrier dysfunction induced by severe trauma

et al.

Abstract: AIM: To investigate the mechanism underlying intestinal barrier function damage after severe trauma and the therapeutic effect of glutamine. METHODS:Burned patients, and animal models of severe trauma replicated by hemorrhagic shock combined with endotoxin infusion and burn injury, were included in a serial experiment. Effects of oral glutamine on intestinal barrier function were observed in scalded rats. Parameters measured in these experiments were as follows: plasma levels of diamine oxidase (DAO), tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Lactadherin is crucially involved in reducing the incidence of RV-associated diarrhea and relevant diarrheal symptoms (4,14,15). Previous studies have demonstrated that breast milk contains lactadherin with a specific sequence, i.e., N'-Arg-Gly-Asp (RGD) crosslinked with integrin α V β 3 and α V β 5 , thus competitively inhibiting the RV combination with host cells (12,(14)(15)(16)(17). The results of the present study demonstrated that, following infection with RV, rats in the groups treated with lactadherin, LBRI and LARI, exhibited less severe diarrheal symptoms, as compared with the RVI group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactadherin is crucially involved in reducing the incidence of RV-associated diarrhea and relevant diarrheal symptoms (4,14,15). Previous studies have demonstrated that breast milk contains lactadherin with a specific sequence, i.e., N'-Arg-Gly-Asp (RGD) crosslinked with integrin α V β 3 and α V β 5 , thus competitively inhibiting the RV combination with host cells (12,(14)(15)(16)(17). The results of the present study demonstrated that, following infection with RV, rats in the groups treated with lactadherin, LBRI and LARI, exhibited less severe diarrheal symptoms, as compared with the RVI group.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were subsequently rinsed three times with PBS for 5 min and developed using 3,3'-diaminobenzidine reagent (Wuhan Boster Biological Technology, Ltd., Wuhan, China). Hematoxylin counterstaining was performed and the specimens were mounted using the conventional method (12). Five fields of view were randomly selected and images of the intestinal mucosal layer were captured using a light microscope (magnification, x40).…”
Section: Immunohistochemical Streptavidin-peroxidase Analysismentioning
confidence: 99%
“…In addition to the liver, intestine also contributes to the systemic inflammatory response and acute phase proteins expression [10] and this intestinal acute phase response may be influenced by protein malnutrition [11,12] . Although glutamine has traditionally been recognized as a nonessential amino acid, recent studies have demon-strated that glutamine plays a major role in the response to injury [13] , in the enterocyte oxidative metabolism [14] , and in the maintenance of the intestinal epithelium [15,16] . Glutamine supplementation may prevent gut mucosal damage and bacterial translocation in various experimental models of gut injury [13,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although glutamine has traditionally been recognized as a nonessential amino acid, recent studies have demon-strated that glutamine plays a major role in the response to injury [13] , in the enterocyte oxidative metabolism [14] , and in the maintenance of the intestinal epithelium [15,16] . Glutamine supplementation may prevent gut mucosal damage and bacterial translocation in various experimental models of gut injury [13,17] . Moreover, glutamine could with stand systemic [18] but also gut-associated [19,20] immune response, because glutamine is an important substrate for optimal lymphocyte [21] and macrophage [22] function.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α content was measured by radioimmunoassay. The activity of diamine oxidase (DAO) in plasma was tested according to the previous report [7] .…”
Section: Stage 3 (1996-2007)mentioning
confidence: 99%